Experimental Evaluation of (L)Au Electron‐Donor Ability in Cationic Gold Carbene Complexes. Issue 71 (20th November 2017) - Carden, Robert G.; Lam, Nathan; Widenhoefer, Ross A.
Abstract: 29 Si NMR spectroscopy was employed to evaluate the electron donor properties of the (L)Au fragments in the cationic gold (β, β‐disilyl)vinylidene complexes [(L)Au=C=CSi(Me)2 CH2 CH2 Si (Me)2 ] + B(C6 F5 )4 − [L=P( t Bu)2 o ‐biphenyl or NHC] relative to the p ‐substituted aryl group in the α‐aryl‐(β, β‐disilyl)vinyl cations [( p ‐C6 H4 X)‐C= CSi(Me)2 CH2 CH2 Si (Me)2 ] + B(C6 F5 )4 − . Similarly, 19 F NMR was employed to evaluate the σ‐ and π‐electron donor properties of the (L)Au fragments in the neutral gold fluorophenyl complexes (L)Au(C6 H4 F) and in the cationic (fluorophenyl)methoxycarbene complexes [(L)AuC(OMe)(C6 H4 F)] + SbF6 − [L=P( t Bu)2 o ‐biphenyl or IPr] relative to the p ‐substituted aryl group of the protonated monofluorobenzophenones [( p ‐C6 H4 X)(C6 H4 F)COH] + OTf − . The results of these studies indicate that relative to p ‐substituted aryl groups, the gold (L)Au fragments [L=P( t Bu)2 o ‐biphenyl or NHC] are significantly more inductively electron donating and are comparable π‐donors and for this reason, the extent of (L)Au→C1 electron donation in gold carbene complexes appears to exceed that provided by a p ‐(dimethyamino)phenyl group. Furthermore, the [L=P( t Bu)2 o ‐biphenyl]Au fragment is a nominally stronger electron donor than the (IPr)Au fragment, and both are significantly more inductively electron donating than the (PPh3 )Au and [P(OMe)3 ]Au fragments. Abstract : Give and you shall receive : Spectroscopic analysis of cationic gold (β, β‐disilyl)vinylidene complexes, gold fluorophenyl complexes, cationic gold flourophenyl(methoxy)carbene complexes, and relevant organic model compounds indicate that (L)Au fragments such as (IPr)Au and [P( t Bu)2 o ‐biphenyl)]Au are strongly inductively electron‐donating, modest π‐donors, and that the net electron‐donor ability of these (L)Au fragments appears to exceed that provided by a p ‐(dimethylamino)phenyl group.